MODERN APPROACH TO INVASIVE CANDIDIASIS DIAGNOSIS AND TREATMENT IN DONOR ORGAN RECIPIENTS (PART II) - E. V. Bolotova; L. V. Shulzhenko; V. A. Porhanov; A. E. Antinyan; O. V. Bozhko; A. A. Smolin (Инновационная медицина Кубани)
In donor organ recipients we observe sufficiently high risk of invasive mycotic infection development and most of them are caused by Candida spp and Aspergillus spp. Clinical evidence of invasive candidiasis are diverse and this fact makes early diagnosis complicated. At the same time, despite relative frequency of invasive mycoses at transplantation, there are no definite recommendations for diagnosis, treatment and prevention of mycotic infections. In most cases physicians should rely on their own clinical experience. In the present study we demonstrated modern approaches to diagnosis and treatment for invasive candidiasis in donor organ recipients.